Evaluation of nutritive value of palm kernel cake fermented with molds as source of protein in ruminant - Wisri Puastuti; Dwi Yulistiani; IWR Susana (Jurnal Ilmu Ternak dan Veteriner, 2014)
The objective of the research was to improve the nutritive value of PKC through fermentation  and to evaluate its degradation characteristics in the rumen and post rumen digestibility as a protein feed source for ruminants. PKC was fermented using Aspergillus niger, Trichoderma viridae and Aspergillus oryzae. To evaluate the in sacco rumen degradability, 2 rumen fistulated females Fries Holstein 3.5 years old were used. Samples were incubated in the rumen for 0, 4, 8, 12, 16, 24, 48 and 72 hours. Determination of dry matter (DM) degradation characteristics value and crude protein (CP) in the rumen was calculated based on formula y = a + b (1 - e-ct). The experiments were conducted using a completely randomized design with four replicates. The results showed that fermentation increased protein content of the PKC by 79.21% with the highest increase from fermentation using Aspergillus oryzae (88.34%). DM and CP degradability ​in the rumen and post rumen of fermented PKC was affected by type of mold used for fermentation. Fermentation increased the amount of water soluble DM (a) of fermented PKC with average of 46.7%, but the value of insoluble but degradable fraction in the rumen (b) was decreased. Fermentation by molds resulited in the reduction of fraction  of insoluble CP but degradable (b) in the rumen by 50.42%. PKC fermentation by Aspergillus oryzae resulted in the higest CP degradability in the rumen and post rumen. It can be concluded that PKC has a high content  of degradable CP in the rumen even without fermentation. Protein source from PKC fermented using Aspergillus oryzae categorized as the best source of feed protein in terms of increasing CP content and digestibility. Key Words: Palm Kernel Cake, Fermentation, Protein, Digestibility